COMPARATIVE STUDY ON SIMILARITIES AND DIFFERENCES OF TEACHING AND LEARNING PROCESS IN PRIMARY SCHOOLS IN INDONESIA AND UZBEKISTAN - Shaturaev, Jakhongir (2014)
This study focused on the comparison on similarities and differences of teaching and learning process in primary schools in Indonesia and in Uzbekistan. Two different developing countries run their own educational policies in primary education. The main purpose of the study was to identify and generally compare similarities and differences between two countries' Primary Education, analyze and reach a deeper understanding of their teaching and learning processes.Since this study was intended to examine the process of teaching and learning in primary schools of two developing countries of Asia named Indonesia and Uzbekistan, it was hoped that this studywould be useful in improving the education policy, making process in both countries studied, and point out better ways of modifying imported educational planning techniques to make them suitable to the realities in Indonesia and as well as in Uzbekistan. Secondly, this study of the applicability of contemporary education planning and policy formulation models to the both countries arena was the first step toward carrying out the much-needed reforms in curriculum. This study utilized a qualitative method approach with four phases of data collection, in which the Researcher collected qualitative data through school observation, interview, questionnaire, and analysis study. Two primary schools in Indonesia and another two primary schools in Uzbekistan were observed for richer data. The results of the study showed that there is significant difference between the Primary Education System of Indonesia and Uzbekistan. Republic of Indonesia runs a 6-3-3 formal education structure, meanwhile, Uzbekistan runs 4-5-3 formal education structure. Another difference in basic education level between two countries is that Education System if decentralized in Indonesia, simultaneously, it remains centralized in Uzbekistan. Nowadays, according to school observation, in Indonesia, student-centered instruction is widely implemented. In elementary schools of Uzbekistan start from 2012, teacher-centered system changed into students-centered system. The teaching methods in urban schools remains same in both countries, by using modern teaching devices each countries is reaching quite high expectations. In outlying areas, it remains as a crucial issue in either Indonesia or Uzbekistan. There are some reformations being taken and new policies have been introduced in both countries to improve quality of education, teacher effectiveness, access to education and teacher trainings. Nevertheless, some crucial issues remain, such as lack of quality teachers, access to education in outlying areas and supplying books and proving teaching-learning gadgets. The findings of the present study offer some recommendations for further research in the same field of inquiry. Despite the fact that this study provides evidence of the issue being investigated and might be useful for basic information for further research, the finding is not exhaustive since a limited number of observations were merely allowed to be conducted due to the factors provided for conducting this study. This study only covers very limited areas and discusses certain points. This study only took four the classroom observation in four different schools in two different countries. Other phenomenon could be found if the classroom observation were done more than four meetings. Penelitianinidifokuskanpadaperbandinganpadapersamaandanperbedaandari proses belajarmengajar di sekolahdasar di Indonesia dan di Uzbekistan. Duanegaraberkembang yang berbedamenjalankankebijakanpendidikanmerekasendiridalampendidikandasar.TujuanutamadaripenelitianiniadalahuntukmengidentifikasidanumumnyamembandingkanpersamaandanperbedaanantaraPendidikanDasarkeduanegara, menganalisisdanmencapaipemahaman yang lebihdalam proses belajarmengajarmereka. Karenastudiinidimaksudkanuntukmenguji proses belajarmengajar di sekolahdasardariduanegaraberkembang di Asia bernama Indonesia dan Uzbekistan, diharapkanbahwapenelitianiniakanbergunadalammeningkatkankebijakanpendidikan, proses pembuatan di keduanegara yang diteliti, danmenunjukkancara yang lebihbaikmemodifikasidiimporteknikperencanaanpendidikanuntukmembuatmerekacocokdenganrealitas di Indonesia danjuga di Uzbekistan. Kedua, penelitianinipenerapankontemporerperencanaanpendidikandanperumusankebijakan model untuk arena keduanegaraadalahlangkahpertamamenujumelaksanakanreformasi yang sangatdibutuhkandalamkurikulum.Penelitianinimenggunakanpendekatanmetodekualitatifdenganempattahappengumpulan data, dimanaPenelitimengumpulkan data kualitatifmelaluiobservasisekolah, wawancara, angket, danstudianalisis.Duasekolahdasar di Indonesia danduasekolahdasar di Uzbekistan diamatiuntuk data lebih kaya.Hasilpenelitianmenunjukkanbahwaadaperbedaan yang signifikanantaraSistemPendidikanDasar Indonesia dan Uzbekistan.Republik Indonesia menjalankan 6-3-3 strukturpendidikan formal, sementaraitu, Uzbekistan berjalan 4-5-3 strukturpendidikan formal.Perbedaan lain di tingkatpendidikandasarantaraduanegaraadalahbahwaSistemPendidikanjikadesentralisasi di Indonesia, secarabersamaan, tetapterpusat di Uzbekistan. Saatini, menurutpengamatansekolah, di Indonesia, instruksi yang berpusatpadasiswasecaraluasditerapkan.Di sekolahdasardari Uzbekistan mulaidaritahun 2012, sistemberpusatpada guru diubahkedalamsistemsiswa-berpusat.Metodepengajaran di sekolah-sekolahperkotaantetapsama di keduanegara, denganmenggunakanperangkatpengajaran modern masing-masingnegaramencapaiharapan yang sangattinggi. Di daerah-daerahterpencil, tetapsebagaiisupentingbaik di Indonesia ataupun Uzbekistan.Ada beberapareformasi yang diambildankebijakanbarutelahdiperkenalkan di keduanegarauntukmeningkatkankualitaspendidikan, efektivitas guru, akseskependidikandanpelatihan guru.Namundemikian, beberapaisukrusialtetap, sepertikurangnya guru yang berkualitas, aksespendidikan di daerah-daerahterpencildanmemasokbukudanmembuktikan gadget belajar-mengajar.Temuandaristudiinimenawarkanbeberaparekomendasiuntukpenelitianlebihlanjut di bidang yang samapenyelidikan. Terlepasdarikenyataanbahwastudiinimemberikanbuktitentangmasalahinisedangdiselidikidanmungkinbergunauntukinformasidasaruntukpenelitianlebihlanjut, temuaninitidaklengkapkarenasejumlahpengamatanhanyabolehdilakukankarenafaktor-faktor yang disediakanuntukmelakukanstudiini .Penelitianinihanyamencakupwilayah yang sangatterbatasdanmembahastitik-titiktertentu.Penelitianinihanyamengambilempatpengamatankelas di empatsekolah yang berbeda di duanegara yang berbeda.Fenomenalaindapatditemukanjikaobservasikelasdilakukanlebihdariempat kali pertemuan.